Do you love me? The relationship between sport-related branded entertainment and brand love - Hildegard Liebl; Jana Turčínková; Rupert Beinhauer; José Magano (Cogent Business & Management, 2022)
Brand love, the most intense relationship between a consumer and a brand, drives valuable outcomes like increased brand loyalty. Sport-related branded entertainment (SRBE) represents a content marketing opportunity to build on brand love and provides a research gap. This research investigates the impact of sport-related branded entertainment on brand love using a mixed-method approach, including a quantitative survey (n~=~372) conducted in Austria, followed by a focus group discussion. A structural equation model revealed a positive impact of SRBE on brand love. Furthermore, brand love is positively associated with brand loyalty, spreading positive word-of-mouth, and the willingness to pay a higher price. Results show that it is most effective in the younger, male, and sporty consumers. Finally, the qualitative focus group discussion revealed deeper insights into consumer motivations. SRBE is a valuable content marketing instrument for brand love. Results revealed that it is most effective in the younger, male, and sporty consumers. The impact of SRBE on brand love has been examined for the first time.
Keywords: 650; brand love; branded entertainment; content marketing; self-expressiveness of brands; Sport-related branded entertainment